Limiares e índices percentuais de reconhecimento de sentenças no ruído, em campo livre, para indivíduos adultos - Henriques, Marília Oliveira (2006)
At the same time that the society has the comfort reached by the evolution in technology, it comes across with something bad that comes from the same evolution: the competitive noise and, consequently, the difficulty with the verbal communication. Moreover, complaints made by individuals who are not being able to comprehend speeches in the presence of noise are becoming more frequent at the audiology clinics, independent of the hearing deficit. Thus, facing the need for dimensioning this difficulty and trying to answer questions referring to the recognition of the speech in the noise, the present study objectives are: to find out the signal-to-noise ratios (S/N) where the sentence recognition thresholds in the noise (SRN) for normal hearing individuals and for individuals with sensorioneural hearing loss; to establish the percentual indexes of sentences recognition in the noise (PISRN) and its variation regarding the S/N ratio, for both groups; to compare the results of both groups. The research was performed by the application of the Portuguese Sentence List Test (COSTA, 1998). The data collection was done between June of 2005 and June of 2006, at the Language and Hearing Sciences Attendance Service of Universidade Federal de Santa Maria (UFSM). Sixty two grown ups individuals with ages between 18 and 64 years old took part of the research, and among them there were 32 normal hearing and 30 individuals with sensorioneural hearing loss from mild degree to moderate-severe, evaluated at an acoustical booth. For this evaluation, the sentences were presented in sound field, at the presence of a competitive noise around 65 dB A. The incidence angle of both the stimulations was of 0º - 0º azimuth. For each person the SRN was obtained. Following this, the PISRN was verified at a fixed intensity equal to or next to the SRN one. Then, the PISRN was researched in S/N ratios with more 2.5 dB and less 2.5 dB from what was established previously. It was noticed that, for the group of people with normal hearing, the SRN were obtained in the S/R ratio of 7.57 dB A and the PISRN was equal to 57.18%. The variation of the PISRN regarding the 2.5 dB favorable alteration around SRN was of increasing 28.43% and regarding the 2.5 dB unfavorable alteration was of 32.18% of reduction. Each 1 dB of variation at the S/N relation represented a change of 12.12% in the PISRN. For the group with hearing loss the SRN were obtained in the S/R ratio of 2.10 dB A and the PISRN was equal to 56%. The variation of the PISRN regarding the 2.5 dB favorable alteration around SRN was of increasing 24.66% and regarding the 2.5 dB unfavorable alteration was of 31.33% of reduction. Each 1 dB of variation at the S/N relation represented a change of 11.20% in the PISRN. There was a difference between the groups for SRN. This difference was not noticed when comparing the PISRN in of both groups, as well as its variation regarding the S/N ratio, both favorable and unfavorable.